The suitability of private equity as an asset class for South African pension funds - Mitha, Kamal (My University, 2016)
ABSTRACT This study examined the suitability of Private Equity as an asset class for South African pension funds. The characteristics were explored as well as the historical performance of the asset class. Although the riskiness of the asset class as well as the liquidity constraints may act as a deterrent for many investors, the diversification benefits as well as the return potential may entice those with a riskier appetite. Numerous studies have been published that have indicated the performance of Private Equity as an asset class. Amongst these studies, a South African study was conducted that used data for the period between January 1992 and December 2003. The study showed that Private Equity outperformed South African listed equities. This current study extended the earlier study for the period between January 2002 and December 2015. This study compared the performance of Private Equity with other asset classes. This study involved a sample of 11 funds based in South Africa covering a 13-year period, ending on 31 December 2015. In comparison to South African listed equities, Private Equity was found to outperform by approximately 15% p.a. The study found Private Equity to have high risk-adjusted returns as well as low correlations with other asset classes, implying diversification benefits. The inclusion of Private Equity into the asset allocation of pension funds was also explored by employing mean variance optimisation. This study found pension funds with the tolerance for risk and limited liquidity needs to add an allocation up to the Regulation 28 limit of 10% to their asset allocation.
MBA Thesis
Keywords: Portfolio management, Investments, Pension trusts -- South Africa.